Spirituality and Revisit Intention in Religious Tourism Tomb of Shaikhona Kholil Bangkalan - Atika, Mery; Ariyani , Yan; Putri , Ivon Valentina (Procedia of Social Sciences and Humanities, 2024)
Religious tourism is one of the tourist destinations that has the potential to be developed in Madura. Pesaraen Tomb of Syaikhona Kholil Bangkalan as a religious tourism destination is ranked first in terms of tourist visits in Madura. Pilgrimages to the graves of the saints are then carried out as a form of respect for the saints where the pilgrims send prayers, make dhikr, and ask Allah SWT for forgiveness for the spirits of the saints. Apart from paying respect, some pilgrims also come with the aim of increasing spirituality. This study aims to find out whether spirituality is related to intention to revisit. The research method used in this research is a quantitative method using the Accidental Sampling technique on pilgrims to the Syaikhona Kholil Tomb, totaling 135 respondents. The data analysis used is the product moment analysis technique. The results of this study show that spirituality is related to the intensity of pilgrims revisiting the grave of Syaikhona Kholil Bangkalan with a significance value of 0.016. Highlights: Spirituality correlates with pilgrims' intention to revisit the Tomb of Syaikhona Kholil. Pilgrims visit for blessings, spiritual connection, and to seek Allah's forgiveness. The Syaikhona Kholil Tomb is the top religious tourism destination in Bangkalan. Keywords: Spirituality, Revisit Intentions, Religious Tourism, Tomb of Shaikhona Kholil Bangkalan